New genera, species and subspecies of tessaratomine true bugs(Heteroptera: Tessaratomidae, Tessaratominae) - Magnien, Philippe (Zootaxa, 2023)
The genus Oukhypencha gen. nov. is described to accommodate Hypencha ophthalmica Stål, 1863, and three new species, O. clemenceae sp. nov., O. florenceae sp. nov., and O. stali sp. nov. A new subspecies, O. ophthalmica sumaterensis ssp. nov. is described from Sumatra. The genus Homoiacoris gen. nov. is created for a new species of tessaratomine true bug from Palawan Island in the Philippines, H. annemarieae sp. nov.. Habitus, male and female genitalia are illustrated. The general aspect of the new genera is similar to that of Hypencha Amyot & Serville, and the main diagnostic characters are found in the genitalia. Keys to genera of the sub-tribe Tessaratomina and species of Oukhypencha are given.